Rock in Rio Business Model – An Exploratory Approach - Ribeiro, T. D.; Ferreira, P. A.; Vaz, Maria João (KISMIF - Keep It Simple, Keep It Fast! - DIY Cultures, Spaces and Places, 2016)
The scope of this paper is the Rock in Rio’s business model. The concept of creating shared value is integrated in it for a better understanding about the sustainability program of the company. The main goal is the construction of Rock in Rio’s business model based on business model canvas. The secondary goals are the analysis of the way the business model works; verify if Rock in Rio apply policies of creating shared value; and if it does, where to place them on the business model. The research is method used was qualitative, focused on a case study. Data were collected from sixteen public interviews with the total length of five hours, and sixteen public documents, a total of ten pages, available in different formats (video, digital and printed). We used content analysis to data processing and delivery of results. We came up with the conclusion that Rock in Rio’s business model is consistent, although it is quite dependent of the partnerships-creation and management. Its communication platform is critical for the success of their business model. The business model building blocks with greater relevance are the customer segments, value proposition and key partnerships. It was not found evidence of the use of creating shared value in the company's sustainability policies. The main limitation found during the investigation was the lack of direct information , due to lack of timely response to the questionnaire sent to Rock in Rio’s , which conditioned the enhanced data triangulation and obtaining information related to the use of creating shared value in the company's sustainability program.